MODEL PENYAJIAN NGELIK PADA KESENIAN JEDORAN DI DUSUN DUKUHAN, RANDUBLATUNG, BLORA - Susilowati, Fajarisma Apri; Fatimah, Mutiara Dewi (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2020)
This research discusses the things behind the emergence of ngelik in Jedoran art and the ngelik presentation model in Jedoran art in Dukuhan Hamlet, Randublatung District, Blora Regency, Central Java. The theory used in this research is the style theory (music) by Alan Lomax and the musical function approach by Alan P. Merriam, which emphasizes the influence of the cultural characteristics of a society on the birth of art in the area and the concept of the function of music in a society's culture. The description of the study aims to find out the things behind the emergence of ngelik in Jedoran art, knowing the presentation model of ngelik in the art of Jedoran Dukuhan. The method used is a qualitative method by interviewing primary sources. Based on the results of this study, it can be concluded that there is ngelik in Jedoran art based on the characteristics and culture of the people who own the art.